2011
DOI: 10.1007/s10552-010-9706-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations of circulating and dietary vitamin D with prostate cancer risk: a systematic review and dose–response meta-analysis

Abstract: Published literature provides little evidence to support a major role of vitamin D in preventing prostate cancer or its progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 60 publications
4
95
0
5
Order By: Relevance
“…This makes a major causal role of vitamin D in prostate cancer unlikely. Our results are in line with a metaanalysis by Gilbert and co-workers, who did not find a significant association of 25-OH-vitamin D levels with total prostate cancer or aggressive prostate cancer risk [20]. The GC rs2282679 variant was furthermore not associated with breast cancer risk [21] or survival from cutaneous melanoma [22].…”
Section: Discussionsupporting
confidence: 91%
“…This makes a major causal role of vitamin D in prostate cancer unlikely. Our results are in line with a metaanalysis by Gilbert and co-workers, who did not find a significant association of 25-OH-vitamin D levels with total prostate cancer or aggressive prostate cancer risk [20]. The GC rs2282679 variant was furthermore not associated with breast cancer risk [21] or survival from cutaneous melanoma [22].…”
Section: Discussionsupporting
confidence: 91%
“…Most importantly, it is increasingly being linked with non-bone related developmental conditions such as schizophrenia [31], multiple sclerosis [32], type 1 diabetes [33], as well as some cancers [34,35]. Therefore, a number of prospective studies have now been undertaken to more closely examine such associations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are inconsistent (Gilbert et al, 2011). Bruggemann (Bruggemann et al, 2010) reported that VD3 inhibited cell growth in vitro, but was not effective against tumor cell growth in the in vivo animal models.…”
Section: Introductionmentioning
confidence: 99%